TANGGUNG JAWAB WALI AMANAT DAN PERLINDUNGAN HUKUM PEMEGANG OBLIGASI BANK GLOBAL INTERNASIONAL - Ota Devy Purnawati; Sharda Abrianti (Reformasi Hukum Trisakti, 2022)
PT Bank Global Internasional Tbk named PT Bank Niaga Tbk as Trustee in the issuance of Subordinated Bonds. The Trustee is the representative of the bondholders in and out of court. The trustee's obligations have been outlined in the Trustee Agreement, Article 51, paragraph 2, of the Capital Market Law, as well as the BAPEPAM Decree. The problem is formulated as to what PT Bank Niaga Tbk's legal obligations are in managing the subordinated bonds of PT Bank Global Internasional Tbk and how the Pension Fund of PT Krakatau Steel is legally protected as the owner of the subordinated bonds of PT Bank Global Internasional Tbk. Standardized research techniques and a literature review Qualitative research methods are generated from secondary data, as are normative research methods and literature study procedures. The findings of the study, discussion, and conclusion that PT Bank Niaga Tbk, as the Trustee, violated the Trusteeship Agreement, UUPM, and BAPEPAM Decisions in carrying out its responsibilities, leading to the non-fulfillment of the bondholders' rights and also to losses for the bondholders-in this case, PT Krakatau Steel Pension Fund-as a result of the non-fulfillment of rights and consequences of losses suffered.